2004
DOI: 10.1037/1072-5245.11.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Work-family concerns of Norwegian police officers: Antecedents and consequences.

Abstract: This research examined (a) potential predictors of work-family conflict and marital partner concerns and (b) consequences of these 2 work-family measures on indicators of psychological and physical well-being. Data were collected, using self-report questionnaires, from 766 male and female police officers in Norway. Job demands and burnout components (exhaustion, cynicism) emerged as strong predictors of the 2 work-family measures. Work-family conflict was also found to have significant negative relationships w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 27 publications
(29 reference statements)
2
79
1
6
Order By: Relevance
“…Support for a reversed relationship was found in a study among 766 police officers in Norway, where job demands and burnout components (exhaustion and cynicism) emerged as strong predictors of work-family conflict (Mikkelsen & Burke, 2004). More generally, and according to Hobfoll (2001), those who lack resources are not only more vulnerable to resource loss, but that initial loss of resources causes future loss.…”
Section: Reversed Effectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Support for a reversed relationship was found in a study among 766 police officers in Norway, where job demands and burnout components (exhaustion and cynicism) emerged as strong predictors of work-family conflict (Mikkelsen & Burke, 2004). More generally, and according to Hobfoll (2001), those who lack resources are not only more vulnerable to resource loss, but that initial loss of resources causes future loss.…”
Section: Reversed Effectsmentioning
confidence: 93%
“…; Mikkelsen, & Burke, 2004). Based on identity theory (Stryker & Burke, 2000) and the resource perspective on the work-home interface (Grawitch, Barber & Justice, 2010;Hobfoll, 2001;ten Brummelhuis & Bakker, 2012), we examine whether work-nonwork conflict and facilitation influence exhaustion and job performance, due to their influence on personal resources of individuals, i.e.…”
mentioning
confidence: 99%
“…Johnson, Todd, & Subramanian, 2005). Burnout has also been linked to health among police officers, both in terms of subjective health complaints (Burke, 1994;Michinov, 2005), medication use, and thoughts of suicide (Berg et al, 2003;Mikkelsen & Burke, 2004). Correlations between burnout and attitudes towards the organization for police, such as job dissatisfaction and desire to leave the job (Burke, 1994;Pines & Keinan, 2005), as well as number of sick days (Mikkelsen & Burke, 2004) have also been reported.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies have also linked burnout to negative outcomes for the families of police officers, such as display of anger and spending time away from the family (Jackson & Maslach, 1982), as well as workfamily conflict (Mikkelsen & Burke, 2004). A recent study of domestic violence in police families indicated that burnout might have both a direct and indirect effect on spouse violence (L. B.…”
Section: Introductionmentioning
confidence: 97%
“…This denial to seek help could be as a result of the perception of the police officer feeling that such help will only reveal to their colleagues their weakness to withstand challenges that go with the job, hence the officers easily fall victim to stress. Mikkelsen and Burke (2004) argue that female police officers are more likely to use emotionally focused coping strategies compared to male police officers who use problem focused coping strategies. Wendy (2008) says that most studies done on police stress and gender focus on male or female officers separately.…”
Section: Relationship Between Gender Of Police Officer and Occupationmentioning
confidence: 99%